Individual, Workplace, and Combined Effects Modeling of Employee Productivity Loss - Stepanek, Martin; Jahanshahi, Kaveh; Millard, Francois (Journal of occupational and environmental medicine, 2019)
OBJECTIVE: Systematically and simultaneously investigate a wide range of influences on workplace productivity loss. METHODS: Data were collected from 31,950 employees in the UK. Influences of employees' socioeconomic characteristics, lifestyle, commuting, physical and mental health, well-being, and job and workplace environment were assessed using structural equation models, allowing systematic decomposition of the complex network of influences and creating new, deeper insights. RESULTS: Mental health, physical health, job characteristics, and support from organization are the most important (direct or indirect) determinants of employees' productivity. 93% of the indirect influences are mediated through mental and/or physical health. Some influences that appear as strong predictors in simple models lose most of their explanatory power in more complex models with additional explanatory variables. CONCLUSIONS: There is a need for a more tailored strategy to improve employees' wellbeing as well as the overall organizational, work, and management culture.
Keywords: pracovní uspokojení; Spojené království; Adolescent; Adult; Job Satisfaction; lidé; lidé středního věku; Personal Satisfaction; Humans; Models, Theoretical; Work Performance; osobní uspokojení; Workplace; Middle Aged; pracovní výkon; Efficiency; duševní zdraví; průzkumy a dotazníky; United Kingdom; Young Adult; pracoviště; cvičení; výkonnost; dospělí; mladý dospělý; mladiství; Exercise; Mental Health; teoretické modely; Surveys and Questionnaires